Biologically relevant small variations of intra-cellular pH can have significant effect on stability of protein–DNA complexes, including the nucleosome - Onufriev, Alexey V. (Frontiers in Molecular Biosciences, 2023)
Stability of a protein-ligand complex may be sensitive to pH of its environment. Here we explore, computationally, stability of a set of protein-nucleic acid complexes using fundamental thermodynamic linkage relationship. The nucleosome, as well as an essentially random selection of 20 protein complexes with DNA or RNA, are included in the analysis. An increase in intra-cellular/intra-nuclear pH destabilizes most complexes, including the nucleosome. We propose to quantify the effect by ∆∆G0.3 – the change in the binding free energy due to pH increase of 0.3 units, corresponding to doubling of the H+ activity; variations of pH of this amplitude can occur in living cells, including in the course of the cell cycle, and in cancer cells relative to normal ones. We suggest, based on relevant experimental findings, a threshold of biological significance of 21 kB T (∼ 0.3 kcal/mol) for changes of stability of chromatin- related protein-DNA complexes: a change in the binding affinity above the threshold may have biological consequences. We find that for 70 % of the examined complexes, ∆∆G0.3 > 21kBT (for 10 % , ∆∆G0.3 is between 3 and 4 kB T ). Thus, small but relevant variations of intra-nuclear pH of 0.3 may have biological consequences for many protein-nucleic acid complexes. The binding affinity between the histone octamer and its DNA, which directly affects the DNA accessibility in the nucleosome, is predicted to be highly sensitive to intra-nuclear pH . A variation of 0.3 units results in ∆∆G0.3 ∼ 10kBT (∼ 6 kcal/mol); for spontaneous unwrapping of 20 bp long entry/exit fragments of the nucleosomal DNA, ∆∆G0.3 = 2.2kB T ; partial disassembly of the nucleosome into the tetrasome is characterized by ∆∆G0.3 = 5.2kB T . The predicted pH - induced modulations of the nucleosome stability are significant enough to suggest that they may have consequences relevant to the biological function of the nucleosome. Accessibility of the nucleosomal DNA is predicted to positively correlate with pH variations during the cell cycle; an increase in intra-cellular pH seen in cancer cells is predicted to lead to a more accessible nucleosomal DNA.